2019
DOI: 10.1590/1413-812320182411.04692018
|View full text |Cite
|
Sign up to set email alerts
|

Interações medicamentosas potenciais em adultos e idosos na atenção primária

Abstract: Resumo O objetivo do presente estudo foi caracterizar as interações medicamentosas potenciais (IMP) e avaliar os fatores associados à sua ocorrência em adultos e idosos assistidos pelo Programa Médico de Família de Niterói, Rio de Janeiro. Trata-se de um subestudo do ESTUDO DIGITALIS, que incluiu indivíduos cadastrados no Programa Médico de Família de Niterói (45-99 anos). Foram analisados 341 indivíduos com prescrição de dois ou mais medicamentos. A classificação das IMP seguiu o MICROMEDEX®. Houve 113 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
1
1
2
Order By: Relevance
“…27 , 28 , 29 Brazilian studies that assessed outpatient population reported higher frequency of moderate potential interactions than severe ones. 30 , 31 Most of the potential interactions in our study were based on poor documentation, similarly to previous research in which half of potential drug interaction relied on fair documentation. 32 , 33 The higher frequency of major severity potential interactions in our population-based sample indicates the potential harms that they can cause to the community.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…27 , 28 , 29 Brazilian studies that assessed outpatient population reported higher frequency of moderate potential interactions than severe ones. 30 , 31 Most of the potential interactions in our study were based on poor documentation, similarly to previous research in which half of potential drug interaction relied on fair documentation. 32 , 33 The higher frequency of major severity potential interactions in our population-based sample indicates the potential harms that they can cause to the community.…”
Section: Discussionsupporting
confidence: 76%
“…Adults aged between 45 and 59 years experienced higher occurrence of potential drug interaction, similarly to previous reports. 30 , 34 , 35 The elderly usually have higher risk of suffering drug interactions, 36 , 37 , 38 but this association was not significant in this study, possibly due to the low number of older participants. We did not observe associations between drug interactions and gender.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…As interações medicamentosas são consequencia de alterações no efeito de um medicamento pela administração prévia ou simultaneamente de outro medicamento, de alimentos, de nutrientes ou até de alguns agentes químicos ambientais (Santos et al, 2019). Destaca-se que há a existência de interações medicamentosas benéficas ou desejáveis, que buscam tratar doenças coexistentes, diminuir efeitos adversos, delongar a duração do efeito, elevar a adesão ao tratamento, impedir ou retardar o aparecimento de resistência bacteriana, incrementar a eficácia ou possibilitar a diminuição de dose (Ferreira et al, 2019).…”
Section: Introductionunclassified
“…Interação medicamentosa (IM) é um processo que ocorre quando os efeitos e/ou toxicidade de um fármaco é modificado pela presença previa ou simultânea de outro fármaco (Santos et al, 2019;Alvim et al, 2015). As IM se classificam em interações físico-químicas, interações farmacocinéticas e interações farmacodinâmicas (Celdran et al,2018).…”
Section: Introductionunclassified